La complejidad de la educación virtual en el proceso de enseñanza aprendizaje de la Historia en el Segundo BGU de la Unidad Educativa Maldonado en el Año Lectivo 2020-2021 - Córdova Ronquillo, Andrés Fabian (2023)
The research focused on the teaching and learning process of History with the aim of understanding the complex processes reflected in virtual education in the teaching and learning of History in the Second General Baccalaureate (BGU) at Pedro Vicente Maldonado Educational Unit during the 2020-2021 academic year. A mixed research methodology was used to analyze statistical and bibliographic data. Surveys and interviews were conducted with 32 students, authorities, and teachers of the institution, and bibliographic information related to the topic was examined. The results showed that both students and teachers faced several complex processes during the teaching and learning process, such as paradigm shifts, adaptation to digital tools, and communication difficulties due to the lack of technological resources. It was concluded that the lack of knowledge about virtual education and the significant technological gap were the main causes of these complex processes. Additionally, the research emphasized the importance of implementing specific virtual tools for the History subject, which could make the class more engaging and foster students' interest in learning. In general, the research highlights the need for further training and support for teachers and students to address the challenges of virtual education in the context of the pandemic and to be prepared in case this modality is used in the future.